2020
DOI: 10.11606/1807-0205/2020.60.14
|View full text |Cite
|
Sign up to set email alerts
|

First survey of the ants (Hymenoptera, Formicidae) of Piauí: filling a major knowledge gap about ant diversity in Brazil

Abstract: Piauí, a Brazilian Northeast state, has been considered one of the most important regions for the presence of new taxa in ants globally, especially considering the ecosystems’ diversity formed by the transition of the three biomes in the state, the Cerrado, Caatinga and the Atlantic Forest. Despite the recent increase in studies of ant diversity in the Neotropical region, Piauí still represents a major knowledge gap regarding its ant fauna. Therefore, this study aimed to increase the knowledge about the ant fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…The most representative genera in this study reflect the results of Jory & Feitosa (2020). These authors also observed Pheidole with the most significant number of species, followed by Solenopsis and Camponotus.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The most representative genera in this study reflect the results of Jory & Feitosa (2020). These authors also observed Pheidole with the most significant number of species, followed by Solenopsis and Camponotus.…”
Section: Discussionsupporting
confidence: 87%
“…The subfamily Myrmicinae was dominant in our study, both in the number of species and in the number of genera. The predominance of Myrmicinae is a general pattern in ant studies in natural environments of the Neotropical Region (Hölldobler & Wilson, 1990;Santos et al, 2017;Silva et al, 2017;Koch et al, 2019), and the state of Piauí is not an exception (Jory & Feitosa, 2020). This subfamily represents about 50% of the diversity of known ant species (Bolton, 2021), and presents flexible feeding habits, behavioral dominance, and varied reproduction strategies (Fernández, 2003;Silvestre et al, 2003;Hamidi et al, 2017), as well as extreme adaptability to control large ecological niches in the Neotropical region (Fowler et al, 1991).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…O gênero Pheidole, o mais diverso dentre os gêneros de Formicidae, apresenta 1003 espécies conhecidas pela ciência, e essa elevada diversidade taxonômica no mundo acarreta em grande diversidade local, pois geralmente é o gênero com maior riqueza de espécies em levantamentos da fauna de formigas brasileira (Vicente et al, 2018;Jory & Feitosa, 2020). Entretanto, apesar de apresentar um comportamento onívoro, esse gênero foi apenas observado no bananal e na agrofloresta.…”
Section: Resultsunclassified